Penerapan Model Problem Based Learning Berbasis STEM Menggunakan Bahan Ajar Realitas Lokal terhadap Literasi Lingkungan Mahasiswa - Nike Anggraini; Khoiron Nazip; Susy Amizera; Elvira Destiansari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effect of applying the Problem Based Learning (PBL) learning model based on Science, Technology, Engineering, and Mathematics (STEM) using environmental teaching materials based on the local reality of South Sumatra to improve students' environmental literacy skills. The method used is Quasi-Experimental Design using Noneqivalent. The research subjects were students of the Biology Education Study Program, FKIP UNSRI. Data analysis was carried out using the MSELS (Middle School Environmental Literacy Survey) questionnaire which was adapted based on local reality teaching materials in South Sumatra. The results showed that the t-count value obtained was 7.832 (> t table = 4.341). In conclusion, the PBL learning model affects increasing students' environmental literacy skills. Keywords: Teaching Materials, Environmental Literacy, PBL, Local Reality, STEM